Multi-omics Analysis Reveals Sequential Roles for ABA during Seed Maturation. Issue 2 (4th April 2019) - Chauffour, Frédéric; Bailly, Marlène; Perreau, François; Cueff, Gwendal; Suzuki, Hiromi; Collet, Boris; Frey, Anne; Clément, Gilles; Soubigou-Taconnat, Ludivine; Balliau, Thierry; Krieger-Liszkay, Anja; Rajjou, Loïc; et al.
Abstract : Hormone and omics analyses during seed development in ABA metabolism mutants highlighted the ABA sequential repression of germination-related processes and its contribution to dormancy depth. Abstract: Abscisic acid (ABA) is an important hormone for seed development and germination whose physiological action is modulated by its endogenous levels. Cleavage of carotenoid precursors by 9-cis epoxycarotenoid dioxygenase (NCED) and inactivation of ABA by ABA 8′-hydroxylase (CYP707A) are key regulatory metabolic steps. In Arabidopsis ( Arabidopsis thaliana ), both enzymes are encoded by multigene families, having distinctive expression patterns. To evaluate the genome-wide impact of ABA deficiency in developing seeds at the maturation stage when dormancy is induced, we used a nced2569 quadruple mutant in which ABA deficiency is mostly restricted to seeds, thus limiting the impact of maternal defects on seed physiology. ABA content was very low in nced2569 seeds, similar to the severe mutant aba2 ; unexpectedly, ABA Glc ester was detected in aba2 seeds, suggesting the existence of an alternative metabolic route. Hormone content in nced2569 seeds compared with nced259 and wild type strongly suggested that specific expression of NCED6 in the endosperm is mainly responsible for ABA production. In accordance, transcriptome analyses revealed broad similarities in gene expression between nced2569 and either wild-type or nced259 developing seeds. Gene ontology enrichments revealed a large spectrum of ABA activation targets involved in reserve storage and desiccation tolerance, and repression of photosynthesis and cell cycle. Proteome and metabolome profiles in dry nced2569 seeds, compared with wild-type and cyp707a1a2 seeds, also highlighted an inhibitory role of ABA on remobilization of reserves, reactive oxygen species production, and protein oxidation. Down-regulation of these oxidative processes by ABA may have an essential role in dormancy control.